2017
DOI: 10.1038/emm.2017.100
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of osteoclast migration and bone resorption by C–C chemokine ligands 19 and 21

Abstract: Osteoclasts are responsible for the bone erosion associated with rheumatoid arthritis (RA). The upregulation of the chemokines CCL19 and CCL21 and their receptor CCR7 has been linked to RA pathogenesis. The purpose of this study was to evaluate the effects of CCL19 and CCL21 on osteoclasts and to reveal their underlying mechanisms. The expression of CCL19, CCL21 and CCR7 was higher in RA patients than in osteoarthritis patients. In differentiating osteoclasts, tumor necrosis factor-α, interleukin-1β and lipopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 49 publications
1
28
1
Order By: Relevance
“…The results suggest that the increased mobility of each osteoclast may amplify matrix‐resorbing activity. This is consistent with a recent report showing that chemokine pathways that activate RhoA and ROCK increase bone resorption in culture without increasing the osteoclast number . To test if the Pfn1 ‐KD osteoclasts are indeed more potent in bone resorption, we knocked down the Pfn1 on bone marrow cells.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The results suggest that the increased mobility of each osteoclast may amplify matrix‐resorbing activity. This is consistent with a recent report showing that chemokine pathways that activate RhoA and ROCK increase bone resorption in culture without increasing the osteoclast number . To test if the Pfn1 ‐KD osteoclasts are indeed more potent in bone resorption, we knocked down the Pfn1 on bone marrow cells.…”
Section: Resultssupporting
confidence: 88%
“…This is consistent with a recent report showing that chemokine pathways that activate RhoA and ROCK increase bone resorption in culture without increasing the osteoclast number. (25) To test if the Pfn1-KD osteoclasts are indeed more potent in bone resorption, we knocked down the Pfn1 on bone marrow cells. By evaluating the pit formation after 6 days of osteoclast induction, we found that the Pfn1-KD osteoclasts resorb more mineralized matrix than those transfected with control siRNA (Supplemental Fig.…”
Section: Pfn1-kd Affects Osteoclast Migration and Matrix Resorptionmentioning
confidence: 99%
“…69,70 Likewise, CCL19 and CCL21 were reported to be higher in RA patients in comparison to osteoarthritis individuals. 69,71 Also, CCL19 has been found at high concentrations in the synovium where it was reported to be expressed by fibroblasts and macrophages. 69,70 In addition, inflammatory molecules such as lipopolysaccharide, TNF-α and IL-1β were found to promote CCR7 expression.…”
Section: Chemokines In Rheumatoid Arthritismentioning
confidence: 99%
“…69,70 In addition, inflammatory molecules such as lipopolysaccharide, TNF-α and IL-1β were found to promote CCR7 expression. 71 Moreover, CCL19 and CCL21 stimulated osteoclast migration as well as bone resorption by osteoclasts in an animal model of RA, 71 and CCL21 drives osteoclastogensis in RA through M1 macrophage polarization of Th17 cells as well as neovascularization. 68 CCL25 and its receptor CCR9 were both detected in the RA synovium.…”
Section: Chemokines In Rheumatoid Arthritismentioning
confidence: 99%
“…Interestingly, many genes stimulating the differentiation and functions of osteoclasts were more highly expressed in MoP tissue compared to ARMD. These include C-C motif chemokine ligand 21 (CCL21) [57], triggering receptor expressed on myeloid cells 2 (TREM2) [58] and creatine kinase B (CKB) [59]. Osteoclast-mediated bone resorption is a known feature of adverse reactions seen in MoM [60] and especially in MoP [22] joints, and polyethylene particles have been demonstrated to promote osteoclastic differentiation of mononuclear cells [61].…”
Section: Discussionmentioning
confidence: 99%